Infant feeding effects on early neurocognitive development in Asian children. Issue 2 (10th December 2014) - Cai, Shirong; Pang, Wei Wei; Low, Yen Ling; Sim, Lit Wee; Sam, Suet Chian; Bruntraeger, Michaela Bianka; Wong, Eric Qinlong; Fok, Doris; Broekman, Birit FP; Singh, Leher; Richmond, Jenny; Agarwal, Pratibha; et al.
ABSTRACT: Background: Breastfeeding has been shown to enhance global measures of intelligence in children. However, few studies have examined associations between breastfeeding and specific cognitive task performance in the first 2 y of life, particularly in an Asian population. Objective: We assessed associations between early infant feeding and detailed measures of cognitive development in the first 2 y of life in healthy Asian children born at term. Design: In a prospective cohort study, neurocognitive testing was performed in 408 healthy children (aged 6, 18, and 24 mo) from uncomplicated pregnancies (i.e., birth weight >2500 and <4000 g, gestational age ≥37 wk, and 5-min Apgar score ≥9). Tests included memory (deferred imitation, relational binding, habituation) and attention tasks (visual expectation, auditory oddball) as well as the Bayley Scales of Infant and Toddler Development, Third Edition (BSID-III). Children were stratified into 3 groups (low, intermediate, and high) on the basis of breastfeeding duration and exclusivity. Results: After potential confounding variables were controlled for, significant associations and dose-response relations were observed for 4 of the 15 tests. Higher breastfeeding exposure was associated with better memory at 6 mo, demonstrated by greater preferential looking toward correctly matched items during early portions of a relational memory task (i.e., relational binding task: P -trend = 0.015 and 0.050 for the first two 1000-ms time bins, respectively). No effects of breastfeeding were observed at 18 mo. At 24 mo, breastfed children were more likely to display sequential memory during a deferred imitation memory task ( P -trend = 0.048), and toddlers with more exposure to breastfeeding scored higher in receptive language [+0.93 (0.23, 1.63) and +1.08 (0.10, 2.07) for intermediate- and high-breastfeeding groups, respectively, compared with the low-breastfeeding group], as well as expressive language [+0.58 (−0.06, 1.23) and +1.22 (0.32, 2.12) for intermediate- and high-breastfeeding groups, respectively] assessed via the BSID-III. Conclusions: Our findings suggest small but significant benefits of breastfeeding for some aspects of memory and language development in the first 2 y of life, with significant improvements in only 4 of 15 indicators. Whether the implicated processes confer developmental advantages is unknown and represents an important area for future research. This trial was registered at www.clinicaltrials.gov as NCT01174875.